Assessment and Spatial Mapping of Soil Degradation Status in Bontoharu District, Selayar Islands Regency: A Framework for Sustainable Land Management - Sudiyanto, I Wayan; Wahyudi, Wahyudi (Jurnal Wasian, 2025)
This research conducts a comprehensive spatial assessment of the soil degradation status in the Bontoharu District, Selayar Islands Regency, to facilitate evidence-based sustainable land management strategies. By employing an integrated methodological framework that combines GIS-based spatial analysis, field surveys, and laboratory testing, the study evaluates various parameters, including physical, chemical, and biological properties of the soil. Key environmental factors examined include rainfall patterns, topography, soil typology, and land use practices. Primary data obtained from field sampling was supplemented with secondary data sources, including CHIRPS rainfall data (2014-2023), digital elevation models, and official land use classifications. The findings indicate that while 81.78% of the study area demonstrates low degradation levels, approximately 18.22% encounters significant soil degradation challenges, with 7.85% classified as very critical. The spatial distribution analysis revealed that surface rock fragments, shallow solum depth, and unfavourable soil physical properties are the predominant limiting factors. The areas most vulnerable to degradation correlate with steep slopes (greater than 45%) and intensive agricultural activities. The study outlines spatially explicit recommendations for targeted conservation interventions, including reforestation in critical areas (1,288.42 hectares), community forest development (1,018.54 hectares), organic matter amendments, and enhancement of land use practices. This research highlights the importance of integrated spatial assessments in formulating location-specific conservation strategies and provides a methodological framework that is applicable to similar island ecosystems facing soil degradation challenges.